Investigating the integrative nature of the Social Competence Inventory - Morrison, Morgan J., author; Heggestad, Eric D., advisor; Clegg, Benjamin, committee member; Thornton, Geroge C., III, committee member; Sarason, Yolanda, committee member (Colorado State University. Libraries, 2005)
In an effort to develop an integrative framework for the multitude of social competence measures developed over the years, Schneider and colleagues (1996, 2002) have created the Social Competence Inventory (SCI), a self-report measure of social competence that encompasses cognitive, trait, and ability components of the construct. The measure is intended to be a broad framework that encompasses more narrow conceptualizations of the construct. This research will investigate the integrative nature of the SCI by simultaneously examining several social competence-related measures, including the recent "hot cognition" of emotional intelligence. The SCI, six other self-report measures of social competence, and the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) were administered to 247 individuals. Joint factor analysis was used to determine whether the MSCEIT and other self-report measures could be represented in SCI factor space. Results indicated that all the extant social competence measures used in this study could be organized under the four SCI factors. The MSCEIT defined a separate fifth factor, suggesting that social competence and emotional intelligence are distinct constructs.
Keywords: psychological tests; quantitative psychology